Gut⁻Liver Axis: How Do Gut Bacteria Influence the Liver? - Konturek, Peter Christopher; Harsch, Igor Alexander; Konturek, Kathrin; Schink, Monic; Konturek, Thomas; Neurath, Markus; Zopf, Yurdagül (Medical Sciences, 2018)
Chronic liver diseases are a major cause of morbidity and mortality worldwide. Recently, gut dysbiosis was identified as an important factor in the pathogenesis of liver diseases. The relationship between gut microbiota and the liver is still not well understood; however, dysfunction of the gut mucosal barrier ("leaky gut") and increased bacterial translocation into the liver via the gut⁻liver axis probably play crucial roles in liver disease development and progression. The liver is an important immunological organ, and, after exposure to gut-derived bacteria via portal circulation, it responds with activation of the innate and adaptive immune system, leading to hepatic injury. A better understanding of the pathophysiological links among gut dysbiosis, the integrity of the gut barrier, and the hepatic immune response to gut-derived factors is essential for the development of new therapies to treat chronic liver diseases.
CRIS-Team Scopus Importer:2023-03-23
Keywords: chronic liver diseases; dysbiosis; gut microbiota